THE USE OF MIME MEDIA TO ENHANCE WRITING OF THE TENTH GRADE STUDENTS OF ISLAMIC SENIOR HIGH SCHOOL ON RECOUNT TEXT - Syahyar Ridhana Putra; Sofyan A. Gani; Kismullah Abdul Muthalib (Universitas Syiah Kuala, 2020)
This study was aimed at finding out the implementation of the mime media to enhance students’ writing skills on recount text at the tenth-grade students of Islamic Senior High School Langsa. This study is quantitative research which used some numerical data that were analyzed statistically. The subjects of this study were 42 students who were taken from X MIA 3 as an experimental group and X MIA 4 as a control group. The instruments used to collect the data were pretest, posttest, and questionnaire. The result of the pretest score in the experimental class was 63.61, and the result of the posttest score in the experimental class was 77. The result of the pretest score in the control class was 63.80, and the result of the posttest score in the control class was 74.47. The test of the hypothesis using the t-test formula showed that the t-count was higher than the t-table. The score of the t-value was 1.72, while t-table on = 5% with df 40 was 1.68, which means the hypothesis was accepted. It could be concluded that there was a different result between the students who were taught by using mime media and those who were not, where the students who were taught by using mime media gained better scores. In the questionnaire, the researchers found that almost all the students choose “agree” toward mime media in writing recount text processes.